Toxocara related peritonitis: A case report and review of literature. (December 2019) - Arslan, Ferhat; Baysal, Naciye Betul; Aslan, Ahmet; Simsek, Bengu Cobanoglu; Vahaboglu, Haluk
Abstract: Toxocariasis is a clinical syndrome caused by the larvae of two ascarid nematodes, namely, Toxocara canis and T. cati that live in dogs and cats as definitive hosts. Humans acquire Toxocara infection by accidental consumption of eggs contaminated foods, soil, water or larvae encapsulated in the viscera or meats of various paratenic hosts e.g., chicken. After oral ingestion, the ova hatch and the free larvae penetrate the intestinal wall to migrate to distant tissues throughout the body. Larvae may also infiltrate the intestinal wall and cause enteritis and mass occupying lesions. Here, we present a T. canis related gastroenteritis and peritonitis case successfully treated with albendazole. We reviewed the literature and found seven previously published Toxocara related peritonitis cases. To our knowledge, this is the first review about non-disseminated toxocariasis that restricted to the intestine and presented as eosinophilic ascites due to peritoneal inflammation. The most common abdominal symptoms were abdominal pain and nausea, and the most common findings were eosinophilic infiltrations on endoscopic biopsy specimens and eosinophilia in the peripheric blood samples. Highlights: Larvae and eosinophilic granulomatous lesions on biopsy diagnose toxocariasis. Serology is an alternative means of diagnosis in human toxocariasis. The presentation may be similar to that of lymphoma or eosinophilic gastroenteritis. Isolated gastrointestinal tract involvement is rare. Patients may present with enteritis and ascites due to eosinophilic inflammation.